Analysis of phosphoproteome in rice pistil. Issue 20 (8th September 2014) - Wang, Kun; Zhao, Yong; Li, Ming; Gao, Feng; Yang, Ming‐kun; Wang, Xin; Li, Shaoqing; Yang, Pingfang
<x xml:space="preserve">Abstract</x> As the female reproductive part of a flower, the pistil consists of the ovary, style, and stigma, and is a critical organ for the process from pollen recognition to fertilization and seed formation. Previous studies on pollen–pistil interaction mainly focused on gene expression changes with comparative transcriptomics or proteomics method. However, studies on protein PTMs are still lacking. Here we report a phosphoproteomic study on mature pistil of rice. Using IMAC enrichment, hydrophilic interaction chromatography fraction and high‐accuracy MS instrument (TripleTOF 5600), 2347 of high‐confidence (Ascore ≥ 19, p ≤ 0.01), phosphorylation sites corresponding to 1588 phosphoproteins were identified. Among them, 1369 phosphorylation sites within 654 phosphoproteins were newly identified; 41 serine phosphorylation motifs, which belong to three groups: proline‐directed, basophilic, and acidic motifs were identified after analysis by motif‐X. Two hundred and one genes whose phosphopeptides were identified here showed tissue‐specific expression in pistil based on information mining of previous microarray data. All MS data have been deposited in the ProteomeXchange with identifier PXD000923 (http://proteomecentral.proteomexchange.org/dataset/PXD000923). This study will help us to understand pistil development and pollination on the posttranslational level.